DAMPAK PERUBAHAN BUDAYA KABUPATEN BUTON SELATAN TERHADAP PEMBELAJARAN DI SEKOLAH DASAR - Haliadi; Anggi; Suci Rahma Wati; Miska Keliobas; Muhammad Ferdin; Rani Alfianita Endang Syah (CV. Adiba Aisha Amira, 2026)
This study examines the impact of cultural change in South Buton Regency on the learning process in elementary schools. The aim is to understand how globalization, modernization, and foreign cultural influences influence traditional values, teaching methods, and student behavior in elementary schools. Using a qualitative approach through interviews, observations, and document analysis, the study found that cultural shifts lead to the loss of local traditions but also introduce innovative educational approaches. The findings suggest that cultural erosion creates challenges in preserving identity but also encourages adaptability and inclusivity in learning. This implies the need to integrate local culture into the curriculum to balance modernization with cultural heritage. The study also emphasizes the importance of inclusive education that combines digital technology with traditional values ​​to increase student motivation and reduce social disparities in rural areas. Furthermore, the study reveals that these changes shape students' character to face global challenges such as digital competition. By focusing on curriculum adaptation, the study provides insights into the role of schools as agents of positive change, promoting cultural tolerance and innovation. The results highlight the need for collaboration between teachers, parents, and the community to maintain local identity while embracing external influences.